1986
DOI: 10.1126/science.3529396
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of Bacterial Lipopolysaccharides (Endotoxins) by a Human Neutrophil Enzyme

Abstract: Lipopolysaccharides in the cell walls of Gram-negative bacteria elicit toxic as well as potentially beneficial inflammatory responses in animals. It is now reported that tissue toxicity caused by lipopolysaccharides is preferentially reduced by an enzymatic activity in human neutrophils. Acyloxyacyl hydrolysis removes fatty acyl chains that are linked to the hydroxyl groups of 3-hydroxytetradecanoyl residues in the bioactive lipid A moiety of the lipopolysaccharides. Maximal acyloxyacyl hydrolysis reduced lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
147
0
5

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(159 citation statements)
references
References 23 publications
7
147
0
5
Order By: Relevance
“…Taken together, these results imply that crayfish haemocytes are able to react differentially to the polysaccharide and lipid A moieties of LPS, where lipid A is cytotoxic and the polysaccharide portion stimulatory. This result agrees with the recognized endotoxic properties of lipid A in LPS [29,30], and the observed reduction of toxicity of deacylated LPS that still possesses potent inflammatory properties in humans [31,32]. The reaction of live haemocytes to LPS Rc, and LPSdex is similar to the reported effects of these molecules on the proPO activation from cell lysates, where LPS Rc was effective in activating the system and LPSdex was not [12].…”
Section: Discussionsupporting
confidence: 87%
“…Taken together, these results imply that crayfish haemocytes are able to react differentially to the polysaccharide and lipid A moieties of LPS, where lipid A is cytotoxic and the polysaccharide portion stimulatory. This result agrees with the recognized endotoxic properties of lipid A in LPS [29,30], and the observed reduction of toxicity of deacylated LPS that still possesses potent inflammatory properties in humans [31,32]. The reaction of live haemocytes to LPS Rc, and LPSdex is similar to the reported effects of these molecules on the proPO activation from cell lysates, where LPS Rc was effective in activating the system and LPSdex was not [12].…”
Section: Discussionsupporting
confidence: 87%
“…During multiplication, destruction and lysis, they release an outer-membrane component, the endotoxin or LPS [68], a thermostable molecule that is a unique structural component of the cell wall of the Gram-negative pathogens. Two phenotypic forms of coliforms with slightly different LPS can be distinguished: smooth with complete LPS sidechains and rough with incomplete LPS side-chains [65,154,169]. Many studies have shown that the pathogenicity of E. coli in the mammary gland is associated with LPS.…”
Section: Endotoxin As Local Mediatormentioning
confidence: 99%
“…A significant detoxification system is acyloxyacyl hydrolase (AOAH), which is present in bovine neutrophil granules [154]. AOAH hydrolyses two acyl chains of the lipid A core of the endotoxin, resulting in a decreased toxicity whereas the immunogenic properties of LPS are largely maintained [169]. In some cows, a decreased blood neutrophil AOAH activity was observed immediately after calving [60].…”
Section: Endotoxin Clearancementioning
confidence: 99%
“…During the saponification, any LPS or lipopeptide would be inactivated because saturated fatty acids acylated in lipid A or lipopeptides will be hydrolyzed. It is well documented that if fatty acids acylated in LPS or lipopeptides are removed, their endotoxic activity is abolished (25)(26)(27). Any LPS or lipopeptide would also be eliminated during the vacuum distillation of fatty acids.…”
Section: Figurementioning
confidence: 99%